2021
DOI: 10.1108/ijchm-06-2021-0767
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence: a systematic review of methods and applications in hospitality and tourism

Abstract: Purpose Several review articles have been published within the Artificial Intelligence (AI) literature that have explored a range of applications within the tourism and hospitality sectors. However, how efficiently the applied AI methods and algorithms have performed with respect to the type of applications and the multimodal sets of data domains have not yet been reviewed. Therefore, this paper aims to review and analyse the established AI methods in hospitality/tourism, ranging from data modelling for demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 88 publications
2
53
0
1
Order By: Relevance
“…The third level of contribution, which we argue returns the highest value, is the application of DL for the development and implementation of novel concepts, business models and product offerings to consumers. Within this level of DL applications, we have seen the development of novel and unique experiences to consumers, for example, AR/VR techniques (Doborjeh et al , 2021; Gaur et al , 2021) and computer-generated imaging (Lee and Madera, 2019; Lin et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The third level of contribution, which we argue returns the highest value, is the application of DL for the development and implementation of novel concepts, business models and product offerings to consumers. Within this level of DL applications, we have seen the development of novel and unique experiences to consumers, for example, AR/VR techniques (Doborjeh et al , 2021; Gaur et al , 2021) and computer-generated imaging (Lee and Madera, 2019; Lin et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Its results confirmed the positive impact of digitalization on firm performance (Chatterjee et al, 2020 ; Ribeiro-Navarrete et al, 2021 ; Zahra, 2021 ), which was particularly visible in the case of our non-family firms. The results showed that digitalization can be one of the core conditions that can lead to increases in firm performance in hospitality organizations where advanced solutions have been adopted (Doborjeh et al, 2022 ; Ivanov & Webster, 2019 ; Salguero & Espinilla, 2018 ). By indicating those dimensions that have not been reflected in the existing EO scholarship and may indeed contribute to a firm’s outcome (namely, flexibility, and digitalization), this study responded to the call that was formulated by Zellweger and Sieger ( 2012 ), who suggested extending the existing EO scales when studying family firms.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of smart restaurant and dining renders as a new phenomenon of interest in foodservice (Peek, 2021). Given the objective stated above, the present research builds the necessary foundation based on three hospitality research areas: service quality (Lin et al , 2020; Wong and Yang, 2020), AI and robots (Doborjeh et al , 2022; Jiang and Wen, 2020; Pillai and Sivathanu, 2020; Fu et al , 2022) and information technology applications in restaurants and other related contexts (Stylos et al , 2021; Law et al , 2022; Mariani and Baggio, 2022). In particular, we seek to synthesize these streams of work to better assess how technologies, especially AI and robots, are infused within the smart restaurants through the lens of service quality.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, AI has been applied to various fields, including management for event lodging, travel agencies, supply chains, restaurants and sales and marketing (Davari et al , 2022; Doborjeh et al , 2022; Fu et al , 2022). AI applications in front-line services may focus on assisting or complementing employees doing more routine tasks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%